Central venous catheter related bloodstream infections in adult patients on home parenteral nutrition: Prevalence, predictive factors, therapeutic outcome. Issue 6 (December 2016) - Santarpia, Lidia; Buonomo, Antonio; Pagano, Maria Carmen; Alfonsi, Lucia; Foggia, Maria; Mottola, Michele; Marinosci, Geremia Zito; Contaldo, Franco; Pasanisi, Fabrizio
Summary: Background: The prevalence of central venous catheter (CVC)-related blood-stream infections (CRBSI), infecting agents and the effectiveness of antibiotic therapy were evaluated in 172 adult patients on Home Parenteral Nutrition (HPN) at the Clinical Nutrition Outpatient Unit of Federico II University Hospital in Naples, Italy. Materials and methods: The study population consisted of 127 oncological (74%) and 45 (26%) non-oncological patients, for a total of 53, 818 (median 104; range 14–1080) CVC days. Results: Ninety-four CRBSIs were diagnosed on 238 CVC (infection rate 1.74/1000 CVC days). Coagulase negative (CoNs) Staphylococci were the most frequently infecting agents (52.8% as single agent) with 17.1% Staphylococcus epidermidis infections. Eighty-three percent S. epidermidis were beta-lattamase producer (BLACT), 66.6% methicillin-resistant (MR) and 55.5% had a MIC for Vancomicin ≥1. Gram-negative bacteria represented 18.6% infections, fungi 7.1%, finally 15% infections were polymicrobial. Previous catheterizations and the presence of an enterocutaneous stoma were significantly related with a higher infection risk ( p < 0.0001 in both cases). Conclusions: CRBSI and antibiotic resistance of infecting agents remain an important challenge in adult patients on HPN; an active research on strategies to counteract the phenomena is required.